2015
DOI: 10.6004/jnccn.2015.0062
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Management of De Novo Stage IV Breast Cancer

Abstract: Management of the intact primary tumor in women presenting with stage IV breast cancer has classically been determined by the presence or absence of symptoms. However, multiple retrospective reviews completed over the past decade suggest a survival advantage with resection of the intact, asymptomatic primary tumor in these women. These reviews are not without bias, and recently completed randomized trials do not

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…Several studies have shown that advanced local surgery may improve survival in women with metastatic breast cancer [ 2 , 9 13 ]. Local resection of the primary tumor remains a positive prognostic factor in metastatic breast cancer even after adjustment for age, tumor burden, site of metastasis, race, type of surgery, margin status, and hormone receptor and HER2 receptor status [ 12 14 ]. A meta-analysis that included 28,693 patients with stage IV breast cancer found that patients who undergo surgical resection of the primary tumor have better survival than patients who do not undergo surgery [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that advanced local surgery may improve survival in women with metastatic breast cancer [ 2 , 9 13 ]. Local resection of the primary tumor remains a positive prognostic factor in metastatic breast cancer even after adjustment for age, tumor burden, site of metastasis, race, type of surgery, margin status, and hormone receptor and HER2 receptor status [ 12 14 ]. A meta-analysis that included 28,693 patients with stage IV breast cancer found that patients who undergo surgical resection of the primary tumor have better survival than patients who do not undergo surgery [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Details of these initiatives are given in the overview by Bayne et al [3]. In breast cancer, similar trials are ongoing or have already completed patient accrual [7]. Preliminary results from a Turkish trial show that the effect of surgery is probably smaller than suggested by the results of the observational studies (ClinicalTrials.gov identifier NCT00557986).…”
mentioning
confidence: 95%
“…Among patients with breast cancer, 5% already have distant metastasis at initial presentation . Systemic therapy is used as the primary treatment for patients with distant metastases, as it results in improved survival and a low‐morbidity rate as compared with surgical procedure.…”
Section: Introductionmentioning
confidence: 99%
“…However, several retrospective studies published over the past decade have suggested that primary tumor resection may result in a better oncologic outcome when used in conjunction with effective systemic therapy . A study based on the National Cancer Database revealed that stage IV patients who underwent surgical intervention at the primary site, with negative margins, demonstrated a statistically significant survival advantage …”
Section: Introductionmentioning
confidence: 99%